2021
DOI: 10.3389/fped.2021.716424
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: The Genetic Diagnosis of Duchenne Muscular Dystrophy in the Middle East

Abstract: The timely and accurate genetic diagnosis of Duchenne muscular dystrophy (DMD) enables prompt initiation of disease management and genetic counseling and optimal patient care. Despite the existence of best practice guidelines for the diagnosis of DMD, implementation of these recommendations in different parts of the world is challenging. Here, we present 4 unique case studies which illustrate the different diagnostic pathways of patients with DMD in Middle Eastern countries and highlight region-specific challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…This resulted in the patients only being reviewed infrequently. A similar challenge with patient visits has recently been reported in the Middle East for patients diagnosed with Duchenne muscular dystrophy, another rare genetic disease (26). There is an unmet need to improve outreach and communication between tertiary and primary care centers so that the patients' local care team is educated on the disease and can help ensure that the patient and their family understand the importance of follow-up care and attendance at hospital appointments.…”
Section: Discussionmentioning
confidence: 83%
“…This resulted in the patients only being reviewed infrequently. A similar challenge with patient visits has recently been reported in the Middle East for patients diagnosed with Duchenne muscular dystrophy, another rare genetic disease (26). There is an unmet need to improve outreach and communication between tertiary and primary care centers so that the patients' local care team is educated on the disease and can help ensure that the patient and their family understand the importance of follow-up care and attendance at hospital appointments.…”
Section: Discussionmentioning
confidence: 83%
“…Other countries do struggle with similar problems as Kazakhstani doctors: delayed diagnosis, funding deficits (22,23). It is difficult to say whether our findings are representative because initially cohorts that do have modified mutations have been involved in the study (preliminarymodified).…”
Section: Discussionmentioning
confidence: 94%
“…The proportion of DMD patients in SA treated with corticosteroids is also considerably lower than in other regions; for example, the Cooperative International Neuromuscular Research Group Duchenne Natural History Study, which took place at 20 study centers across nine countries between 2006 and 2016, reported that 87% of patients received corticosteroid treatment ( 16 ), and the STRIDE Registry reported that 89.2% of patients received corticosteroid treatment ( 15 ). The reasons for low corticosteroid use in SA are not clear, but may include region-specific concerns in the Middle East regarding corticosteroid side effects ( 9 , 17 ).…”
Section: Discussionmentioning
confidence: 99%